Improvising Friendship - Stewart, Jesse (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Jesse Stewart reflects on his friendship with Ajay Heble, including reflections on the various projects on which they've collaborated over the years.